Effects of Wheat Protein-based Herbal Shampoo and Comparison with Commercial Shampoo - Harsh Singh (International Journal of Pharma and Bio Sciences, 2021)
The primary objective of this experiment is to study and observe the effects of Wheat- protein based herbal shampoo containing natural ingredients and to evaluate and compare its physicochemical properties with commercial synthetic shampoos. An attempt has been made to observe the effects of protein shampoo with natural ingredients that might help bring rough & dry hair back to normal, make it softer and healthier. The study showed that the herbal shampoo clears dirt, dandruff, promotes hair growth, strengthens and darkens the hair; it also acts as a conditioning agent and performs all these actions without affecting or damaging hair. The shampoo consists of extracts of Wheat Sprouts (it tends to repair capillaries to get strong & thick hair), Wheat Grass (treats dandruff & scalp problems), Aloe vera (helps in thickening of hair), China Rose (makes hair smooth and shiny), Bhringraj (helps retain black color of hair), and Retha (is a cleansing agent) in different proportions. Various physicochemical and performance tests for herbal shampoo & commercial shampoo were carried out in terms of visual inspection, wetting time, pH, percentage of solid contents, surface tension, detergency, dirt dispersion, conditioning performance. The formulated protein shampoo was evaluated for conditioning performance by its application in 20 volunteers. The formulated herbal shampoo is yellow in color with demonstrable good detergency, cleansing property and surface tension. The pH of protein shampoo was 6.5, near to skin pH. Percentage of solid content of shampoo was found to be 21% after drying. Dirt dispersion of formulated herbal shampoo was light. 1% of shampoo gave 23 cm foam height and viscosity of 42.5 milli poise. The highest score of the conditioning performance of the developed protein shampoo was found to be 3 out of 4. All these are ideal characters for a good quality herbal shampoo to be used in daily life without any side effects as compared to the available commercial shampoos and optimum for hair care. However, further work is required to improve its quality and observing its overall effects.